Implementasi Peraturan Presiden Nomor 104 Tahun 2007 Tentang Penyediaan, Pendistribusian Dan Penetapan Harga Liquified Petroleum Gas Tabung 3 Kilogram - Neni Suryanti; Muhammad A Rauf (Pattimura Legal Journal)
Introduction: Kerosene to Liquified Petroleum Gas (LPG) conversion program as part of the Indonesian government's strategy to reduce kerosene subsidies and improve budget efficiency.